2015
DOI: 10.3109/03091902.2015.1040895
|View full text |Cite
|
Sign up to set email alerts
|

The coated antiseptic tip (CAT) syringe

Abstract: Catheter-related blood stream infections (CR-BSI) account for 30% of healthcare acquired infection (HAI). Colonization of connector hubs and contaminated syringes are thought to increase the risk of CR-BSI. The Coated Antiseptic Tip (CAT) syringe was developed to decontaminate connector hubs, thereby reducing the risk of CR-BSI. Needleless valves (n = 20) and three-way connectors (n = 20) were contaminated with common critical care pathogens. At hourly intervals, CAT syringes were inserted into the connector h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…An alternative design has been proposed by Buchmann et al (2009) whereby the cap encapsulates the entire terminal end of the NFC including the thread ( Figure 4 B) and, in contrast to the simple insert cap highlighted in Figure 4 A, is intended to remain attached during flush procedures [ 85 ]. Mariyaselvam et al (2015) reported that contamination of syringe tips is an often overlooked factor in the development of CRBSI and hence retention of the antimicrobial foam as a secondary septum could aid in the decontamination of the tips prior to entering the NFC [ 86 ].…”
Section: Current Practicementioning
confidence: 99%
“…An alternative design has been proposed by Buchmann et al (2009) whereby the cap encapsulates the entire terminal end of the NFC including the thread ( Figure 4 B) and, in contrast to the simple insert cap highlighted in Figure 4 A, is intended to remain attached during flush procedures [ 85 ]. Mariyaselvam et al (2015) reported that contamination of syringe tips is an often overlooked factor in the development of CRBSI and hence retention of the antimicrobial foam as a secondary septum could aid in the decontamination of the tips prior to entering the NFC [ 86 ].…”
Section: Current Practicementioning
confidence: 99%